Association of frailty index with perioperative mortality and in-hospital morbidity after elective lower extremity bypass - Eslami, Mohammad H.; Saadeddin, Zein; Rybin, Denis V.; Doros, Gheorghe; Siracuse, Jeffrey J.; Farber, Alik (Journal of vascular surgery, 2019)
The frailty index has been linked to adverse outcomes after surgical procedures. In this study, we evaluated the association between frailty index and outcomes after elective lower extremity bypass (LEB) for lower extremity ischemia. The American College of Surgeons National Surgical Quality Improvement Program data set (2005-2012) was used to identify patients who underwent elective LEB using diagnostic and procedure Current Procedural Terminology codes. Modified frailty index (mFI) scores, derived from the Canadian Study of Health and Aging, were categorized into three groups: low, medium, and high. Association of mFI with 30-day postoperative death (POD), myocardial infarction (MI), cardiopulmonary events (CPEs), deep tissue surgical site infection (SSI), and graft failure (GF) was evaluated. Both univariate and multivariable regression analyses—adjusted for age, sex, American Society of Anesthesiologists class, body mass index, and creatinine levels—were used to assess the effect of frailty on each outcome. Of 12,677 patients (mean age, 67.7 ± 11.1 years) identified who underwent elective LEB, POD occurred in 265 (2.1% overall). Postoperative MI, SSI, CPEs, and GF occurred in 1.6%, 2.5%, 3.1%, and 4.3%, respectively. The mean mFI of the entire sample was 0.3 ± 0.1. Adjusted odds ratio for development of any morbidity in the group with the highest mFI was 1.36 (95% confidence interval, 1.08-1.72; P = .010) compared with the low frailty group. Patients with higher mFI were more likely to develop MI and CPEs but not SSI or GF. Univariate and multivariable analyses showed a significantly increased risk of POD among those in the highest mFI tertile. Female sex and age, increased American Society of Anesthesiologists class and creatinine levels, and decreased body mass index independently predicted increased mortality. The addition of categorical mFI improved models with these variables. Higher mFI is independently associated with higher mortality and morbidity. Preoperative mFI assessment may be considered an additional screening tool for risk stratification among patients undergoing LEB.